Comparative study of test kits for measurement of rheumatoid factors by the latex fixation test. Issue 10 (October 1990) - Klein, F; Janssens, M B; van Romunde, L K; Eilers, G A
Abstract : The performance of 14 test kits for the measurement of rheumatoid factors by the latex fixation test was investigated; all results were expressed in IU/ml. Reproducibility and properties of control sera were also studied. It was found that half of the kits did not satisfactorily detect rheumatoid factor levels lower than 25 IU/ml. Most kits performed reasonably well in practice. Positive control sera only rarely met strict requirements. The relative costs did not always have a clear correlation with the quality of the results. The variation caused by differences between kits became acceptable when the results were expressed in IU/ml.